Collective memory, unconscious transmission, and regulations: on the problem of memory and social bonds (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The purpose of this article is to critically and comprehensively approach Halbwachs' concept of Collective Memory, with the aim of recognising: i) the current relevance of this concept with respect to contemporary social issues, where dominant and subaltern experiences and memories are combined within complex processes of individuation, transgenerational transmission and normative constitution of societies, ii) to compare the treatment of the concept of collective memory from the theorisations present in Halbwachs, Freud and Canguilhem, in order to identify possible lines of discussion between these perspectives. For this purpose, primary sources of the main authors of the study are established as main discussion coordinates, which are complemented and discussed with contemporary appropriations of these works.
Keywords: Collective memory; Normativity; Transmission transgenerational; Psychoanalysis